Association of Sleep Duration with Obesity among US High School Students - Lowry, Richard; Eaton, Danice K.; Foti, Kathryn; McKnight-Eily, Lela R.; Perry, Geraldine; Galuska, Deborah A. (Journal of Obesity, 2012)
Increasing attention is being focused on sleep duration as a potential modifiable risk factor associated with obesity in children and adolescents. We analyzed data from the national Youth Risk Behavior Survey to describe the association of obesity (self-report BMI ≥95th percentile) with self-reported sleep duration on an average school night, among a representative sample of US high school students. Using logistic regression to control for demographic and behavioral confounders, among female students, compared to 7 hours of sleep, both shortened (≤4 hours of sleep; adjusted odds ratio (95% confidence interval), AOR = 1.50 (1.05–2.15)) and prolonged (≥9 hours of sleep; AOR = 1.54 (1.13–2.10)) sleep durations were associated with increased likelihood of obesity. Among male students, there was no significant association between obesity and sleep duration. Better understanding of factors underlying the association between sleep duration and obesity is needed before recommending alteration of sleep time as a means of addressing the obesity epidemic among adolescents.